Feasibility of E-module on Fungi Based on Mushroom Diversity in Sebubus Forest, Sambas Regency - Azijah Azijah; Fitri Laili Yeni; Afandi Afandi (Universitas Sultan Ageng Tirtayasa, 2026)
The limited time available to deliver the “Fungi and Their Roles” topic and the lack of classroom materials to support its learning are obstacles that can hinder holistic biology learning. An e-module integrated with local mushroom diversity is one option for learning media that can support contextual learning on fungi. This research aims to assess the feasibility of an e-module on mushroom diversity in the Sebubus Forest, Sambas Regency, as an innovative and contextually relevant biology learning medium. The applied research and development method used the Define, Design, Develop, and Disseminate (4D) model, limited to the third stage. The e-module was validated by five validators using five assessment criteria. The results of the validation data analysis showed that the five assessment criteria obtained a Content Validity Ratio score of 0.99 and were considered valid. The Content Validity Index score based on the five criteria was 0.99, which is the threshold, indicating that the e-module on mushroom diversity in the Sebubus Forest, Sambas Regency, is valid and suitable for learning, especially in the topic of “Fungi and Their Roles.” By leveraging local biodiversity, this e-module is expected to enhance students’ understanding of fungi, particularly mushrooms, and their diversity.